Application of Plant Metabonomics in Quality Assessment for Large-Scale Production of Traditional Chinese Medicine - Ning, Zhangchi; Lu, Cheng; Zhang, Yuxin; Zhao, Siyu; Liu, Baoqin; Xu, Xuegong; Liu, Yuanyan (Planta Medica, 2013)
The curative effects of traditional Chinese medicines are principally based on the synergic effect of their multi-targeting, multi-ingredient preparations, in contrast to modern pharmacology and drug development that often focus on a single chemical entity. Therefore, the method employing a few markers or pharmacologically active constituents to assess the quality and authenticity of the complex preparations has a number of severe challenges. Metabonomics can provide an effective platform for complex sample analysis. It is also reported to be applied to the quality analysis of the traditional Chinese medicine. Metabonomics enables comprehensive assessment of complex traditional Chinese medicines or herbal remedies and sample classification of diverse biological statuses, origins, or qualities in samples, by means of chemometrics. Identification, processing, and pharmaceutical preparation are the main procedures in the large-scale production of Chinese medicinal preparations. Through complete scans, plants metabonomics addresses some of the shortfalls of single analyses and presents a considerable potential to become a sharp tool for traditional Chinese medicine quality assessment.
Keywords: plant metabonomics; large-scale production; discrimination; processing; pharmaceutics